Identifying the Link Between Coastal Tourism and Marine Ecosystems in the Baltic, North Sea, and Mediterranean Countries - Vladimir Otrachshenko; Francesco Bosello (Fondazione Eni Enrico Mattei (FEEM), 2015)
This paper examines the impact of marine ecosystem quality on inbound coastal tourism in the Baltic, North Sea, and Mediterranean countries. Given extensive empirical findings in ecological science, we use marine protected areas (MPAs) and the fraction of species that are shed in each country's exclusive economic zone that are overexploited or collapsed as a proxy for marine ecosystem quality. We use an autoregressive distributed lag model in a destination-origin panel set up. The empirical findings of this paper suggest that MPAs have a negative direct effect on tourism. However, this effect is reversed when the interaction terms with economic variables are included. Also, by using the fraction of species that are overexploited as an indicator of the deterioration of marine ecosystem quality, we find a considerable negative impact of this index on inbound coastal tourism. The short-term (current) impact of this index on tourism constitutes less than half of the long-term impact. Results provide valuable information for policy makers, suggesting that measures enhancing marine ecosystem quality should be considered in addition to conventional tourism policies focused on price.
Keywords: C33; Q57; Q26; 330; Coastal Tourism; Marine Ecosystem Quality; Panel Data